Colonial Life in Conrad’s The Heart of Darkness And Forster’s a Passage to India (A Comparative Based on Sociological Perspective) - Fauzi Razak (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The Industrial Revolution was a time of great age throughout the world. It represented major change from 1760 to the period 1820-1840. The movement originated in Great Britain and affected everything from industrial manufacturing processes to the daily life of the average citizen. The main industry at the time was the textile industry. It had the most employees, output value, and invested capital. It was the first to take on new modern production methods. The effects caused by the industrial revolution which has mentioned above, can lead to another impact such as the emergence of where the industry must obtain the availability of raw materials, and the next impact is where the result of the raw material processess by the industry will be marketed. For colonialism itself, generally it is the direct and overall domination of one country by another on the basis of state power being in the hands of a foreign power. Spesifically colonialism has two objectives, they are political domination and the second one is to make possible the exploitation of colonized country. This research aims to find out the colonialisms traits of the characters perform in their respective position, and to reveal the impacts of colonialism on characters.